TINJAUAN YURIDIS TERHADAP OBJEK TANAH TERLANTAR ATAS HAK GUNA USAHA (HGU) PERKEBUNAN DI KABUPATEN KUTAI TIMUR - Siti Nurmaya Sari (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACT This study aims to find out the neglected land designation for plantation use rights in East Kutai Regency and to find out the legal consequences of the determination of the abandoned land object.This research is a type of empirical juridical legal research. Data collection is done by asking for data and interview methods. This research was conducted at the Regional office of the National Land Agency of the Province of East Kalimantan Based on the research result obtained from this paper, it can be concluded that: 1) Determination of abandoned land objects in East Kutai district based on cultivation Rights is carried out by means of, among others, inventory, identification and research of abandoned land and giving a warning to be designated as abandoned land by the head the republic of Indonesia Land Agency which has not yet been realized 2) At PT Sumber Kharisma Persada has not had any legal consequences because there has been no response or response from the BPN of the republic of Indonesia, if referring to Article 9 paragraph (2) and paragraph (3) PP No. 11 of 2010 concerning Control and utilization of Neglected Land, PT SumberKharismaPersada will get legal consequences, namely the termination of the relationship between the subject of the rights holders and land objects, then the land will be re-controlled by the state. Land indicated as abandoned must be regulated according to government Regulation No. 11 of 2010 concerning control and utilization of neglected land.  Keywords : Abandoned Land Object, Cultivation Right